Pengaruh Dosis Ekstrak Daun Mengkudu (Morinda citrifolia) Terhadap Serangan Ektoparasit Pada Ikan Nila (Oreochromis niloticus) - WaOde Safia; Budiyanti; Razak (AquaMarine (Jurnal FPIK UNIDAYAN ), 2022)
This study aims to determine the effect of noni leaf extract doses on inhibiting ectoparasitic attacks on tilapia (Oreochromis niloticus). Parasite identification is carried out at the Fish Quarantine Station for Quality Control and Safety of Fishery Products in Baubau. The test fish used were tilapia seeds infected with ectoparasites with a size of 7-10 cm at a density of 12 fish/container. The study used a completely randomized design (CRD) with 4 treatments and 3 replications, namely soaking noni leaf extract for 30 minutes. Data analysis using Analysis of Variance (ANOVA). The results showed that the administration of noni leaf extract had a significant effect on the intensity (ind/head) and % ectoparasites prevalence but the survival rate (SR) of tilapia (Oreochromis niloticus). From the research results found 7 types of ectoparasites namely Chilodonella sp, Oodinium sp. Gyrodactylus sp, Vorticella sp, Epistilis sp, Argulus sp, and Tricodina sp. Treatment B 20% immersion and C 30% immersion gave the best intensity and prevalence values with intensity values of 1.7 ind/head and 1.8 ind/head. As well as prevalence values of 88.87% and 44.40%.